Quality Management In Islamic Education And Its Implementation In The Development Of Madrasah And Boarding School - Wahyu Hidayat; Martin Kustati; Nana Sepriyanti; Nurhasnah, Nurhasnah (International Journal of Education, Vocational and Social Science, 2024)
This paper will focus on "Quality Management in Islamic Education and its Implementation in the Development of Madrasahs and Islamic Boarding Schools". The quality of education is one of the central issues of national education in addition to issues of equity, relevance, and efficiency of education management. Today, many efforts to improve the quality of education continue to be made by various parties. These efforts are based on an awareness of the important role of education in the development of human resources and the development of national character (Nation Character Building) for the progress of society and the nation. The type used in this research is library study research (library research) where this library research is carried out by researchers not going directly to the field but this research is carried out through research on written works and various kinds of literature available, be it through books, journals, and so on. The results can be concluded that the implementation of quality management in madrasah and pontren is; a). Continuous improvement in meeting customer needs with the involvement of all members of the organization. b). Efforts to maximize the competitiveness of institutions to improve products, services, people, labor, processes and the environment. c). As a means in the learning process. d). Overall supervision of organizational members.